2014
DOI: 10.1186/s13054-014-0660-4
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D deficiency as a risk factor for infection, sepsis and mortality in the critically ill: systematic review and meta-analysis

Abstract: IntroductionIn Europe, vitamin D deficiency is highly prevalent varying between 40% and 60% in the healthy general adult population. The consequences of vitamin D deficiency for sepsis and outcome in critically ill patients remain controversial. We therefore systematically reviewed observational cohort studies on vitamin D deficiency in the intensive care unit.MethodsFourteen observational reports published from January 2000 to March 2014, retrieved from Pubmed and Embase, involving 9,715 critically ill patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
184
5
8

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(205 citation statements)
references
References 42 publications
8
184
5
8
Order By: Relevance
“…Additionally, it was also documented that a relationship between vitamin D deficiency and increased mortality in community-acquired pneumonia (CAP) and sepsis was found [13][14][15][16]. Despite the increasing number of studies about CAP, there are scarce data about VAP, and to our knowledge, there are no studies related to the effects of vitamin D on specific pathogens such as XDR A. baumanii in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it was also documented that a relationship between vitamin D deficiency and increased mortality in community-acquired pneumonia (CAP) and sepsis was found [13][14][15][16]. Despite the increasing number of studies about CAP, there are scarce data about VAP, and to our knowledge, there are no studies related to the effects of vitamin D on specific pathogens such as XDR A. baumanii in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…53 VDD <50 nmol/L represents a serious risk factor for infection, sepsis, and mortality in critically ill patients, as it increases susceptibility for severe infections and mortality. 54 This link between VDD and inflammatory biomarkers is also found in patients with multiple sclerosis, rheumatoid arthritis, and advanced age. 55 An interesting link among vitamin D, immunity, insulin resistance, and CVD was revealed in laboratory mice when researchers genetically eliminated macrophage VDRs and the mice developed arterial atherosclerotic plaques and insulin resistance due to hepatic and vascular inflammation.…”
Section: Increased Risk and Poor Outcomes For Ischemic Strokementioning
confidence: 89%
“…Depending to that analysis, it was reported that severe infection and mortality rates were high in vitamin D deficiency. In that analysis, risk for nosocomial infection development and intubation status were not evaluated (26).…”
Section: Discussionmentioning
confidence: 99%